Cognitive Therapy Alone and in Combination with Antidepressants for Anxious Depression: A STAR*D Report - Farabaugh, Amy (2012)
BACKGROUND: Anxious depression, defined as MDD with high levels of anxiety, has been associated with lower rates of antidepressant response and remission as well as greater chronicity, suicidality and antidepressant side-effect burden. The primary aim of this study was to assess the effectiveness of cognitive therapy (CT) alone or in combination with medications for anxious versus non-anxious depression. METHODS: We assessed the STAR*D study participants who were partial or non-responders to citalopram. Subjects were then either switched (n = 696) to a new antidepressant or to CT alone, or they were kept on citalopram and augmented (n = 577) with another antidepressant or CT. We compared response and remission rates of those who met criteria for anxious depression to those who did not across treatment conditions. RESULTS: Those with anxious depression had significantly lower remission rates based on the QIDS, whether assigned to switch or augmentation, compared to those with non-anxious depression. Those with anxious depression, compared to those without, had significantly lower response rates based on the QIDS only in the switch group. There was no significant interaction between anxious depression and treatment assignment. LIMITATIONS: Limitations include the use of citalopram as the only Level 1 pharmacotherapy and medication augmentation option, depression-focused CT rather than anxiety-focused CT, and focus on acute treatment outcomes. CONCLUSIONS: Individuals with anxious depression appear to experience higher risk of poorer outcome following pharmacotherapy and/or CT after an initial course of SSRI, and continued efforts to target this challenging form of depression are needed.